Manufacturing and design of smart polymer composites - Saba, Farooq; Zainab, Ngaini; Sana, Farooq (Elservier, 2021)
Smart polymers (SP) have been extensively developed for inventive and valuable resolutions in diverse applications such as in the electrical and biomedical fields. Numerous synthetic techniques that have been introduced to form unique smart polymers with desired properties (e.g., size, shape, and geometry) are discussed. Specific design of SP is a prerequisite for specific applications, which is a fundamental and significant factor to acquire structures with desired properties. In this chapter, a comprehensive review of the basic manufacturing and designing of smart polymers is discussed to provide elementary information about physical, chemical, and biological modes along with physiochemical processing for designing SP. This chapter also describes the advancement in technology for the synthesis of smart polymers in a systematic and efficient methodology to benefit mankind.